Phylogenetic composition and properties of bacteria coexisting with the fungus Hypholoma fasciculare in decaying wood - Valásková, Vendula; de Boer, Wietse; Gunnewiek, Paulien J A Klein; Pospísek, Martin; Baldrian, Petr (The ISME journal, 2009)
White-rot fungi are major degraders of woody materials in terrestrial environments because of their ability to decompose lignin. However, little is known on the possible associations of white-rot fungi with other microorganisms during wood decay. We investigated the numbers, community composition and functional traits of bacteria present in natural wood samples under advanced decay by the white-rot basidiomycete Hypholoma fasciculare. The wood samples contained high numbers of cultivable bacteria (0.2-8 x 10(9) colony forming units (CFU) per g of dry wood). Most cultivable bacteria belonged to Proteobacteria and Acidobacteria (75% and 23% of sequences, respectively). The same phyla were also found to be dominant (59% and 23%, respectively) using a non-culturable quantification technique, namely, direct cloning and sequencing of 16sRNA genes extracted from wood. Bacteria that could be subcultured consisted of acid-tolerant strains that seemed to rely on substrates released by lignocellulolytic enzyme activities of the fungus. There were no indications for antagonism (antibiosis) of the bacteria against the fungus.
Keywords: Sequence Analysis, DNA; DNA, Ribosomal; sekvenční analýza DNA; Agaricales; Phylogeny; shluková analýza; RNA ribozomální 16S; dřevo; Cluster Analysis; DNA, Bacterial; Molecular Sequence Data; RNA, Ribosomal, 16S; DNA bakterií; fylogeneze; Wood; ribozomální DNA; Bacteria; molekulární sekvence - údaje